Experimental Study on Strength and Performance of Foamed Concrete with Glass Powder and Zeolite - Al-Khazaleh, Mahmoud; Krishna Kumar, P.; Qtiashat, Deya; Alqatawna, Ali (Civil Engineering Journal, 2024)
Cement manufacturing accounts for approximately 7% of anthropogenic CO₂ emissions. To mitigate environmental impact and achieve “net zero” by 2050, developing cementitious materials that minimize cement consumption is crucial. This research aims to reduce cement usage in Foamed Concrete (FC). The study investigates the mechanical, durability, and thermal properties of FC using two distinct Supplementary Cementitious Admixtures (SCA): Glass Powder (GP) and natural zeolite. Cement was replaced with SCA at varying percentages (0%, 5%, 10%, 15%, 20%, and 25% by weight) in FC. The FC density was adjusted by incorporating foam at 15% and 30% of the total volume of concrete. The study evaluated the flowability of each mix in its fresh state. The mechanical properties were assessed by measuring compressive strength and ultrasonic pulse velocity. The performance of FC was further analyzed in terms of thermal conductivity, sorptivity, and water absorption. The test results revealed that FC with GP combinations exhibited high flowability and an improved strength-to-density ratio. Additionally, water absorption, sorptivity, and thermal conductivity were significantly reduced compared to conventional FC. An extensive cost-benefit analysis highlighted the feasibility of utilizing common waste materials to produce high-grade FC and assessed the impacts of cementitious admixtures as viable alternatives to cement. Doi: 10.28991/CEJ-2024-010-12-06 Full Text: PDF